2006
DOI: 10.1176/appi.ps.57.5.716
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maternal Mental Health Problems on Child Treatment Response in Community-Based Services

Abstract: These findings suggest that treatment for mothers as well as children could be beneficial for this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…In fact some research suggests that treating parental issues, especially psychopathology, simultaneously, prior to or even instead of child treatment can improve child behavior problems and parenting efficacy (Gunlicks and Weissman 2008; Pilowsky et al 2008; Rishel et al 2006; Weaver et al 2008). It is suggested that a clinician must understand client characteristics related to P/FCFs so that decisions can be made to provide a treatment plan tailored to the needs of the entire family.…”
Section: Discussionmentioning
confidence: 99%
“…In fact some research suggests that treating parental issues, especially psychopathology, simultaneously, prior to or even instead of child treatment can improve child behavior problems and parenting efficacy (Gunlicks and Weissman 2008; Pilowsky et al 2008; Rishel et al 2006; Weaver et al 2008). It is suggested that a clinician must understand client characteristics related to P/FCFs so that decisions can be made to provide a treatment plan tailored to the needs of the entire family.…”
Section: Discussionmentioning
confidence: 99%
“…Parent mental health problems influence the course and outcomes of child problems (Rishel et al 2006), so attempts to influence behavior may need to be directed to parents as well as to children, including motivating parents to seek care for their own emotional or behavioral difficulties. In child psychotherapy, alliance between therapist and parent predicts attendance at treatment sessions, but alliance with children predicts treatment outcome (Hawley and Weisz 2005).…”
Section: Provider Awareness Of Family Attitudes and Expectationsmentioning
confidence: 99%
“…Parents who bring their children to mental health clinics frequently manifest high rates of mental health difficulties themselves (Ferro, Verdeli, Pierre, & Weissman, 2000; Rishel, Greeno, Marcus, & Anderson, 2006; Swartz et al, 2005). However, many of these parents do not receive their own psychiatric treatment (Ferro et al, 2000; Swartz et al, 2005), which can result in negative treatment outcomes for their children (Brent et al, 1998; Rishel et al, 2006).…”
mentioning
confidence: 99%
“…However, many of these parents do not receive their own psychiatric treatment (Ferro et al, 2000; Swartz et al, 2005), which can result in negative treatment outcomes for their children (Brent et al, 1998; Rishel et al, 2006). Parental depression, in particular, can have deleterious consequences in terms of child disruptive behavior difficulties (Aikens, Coleman, & Barbarin, 2007; Cummings, Keller, & Davies, 2005; Marchand, Hock, & Widaman, 2002).…”
mentioning
confidence: 99%